Cervical cancer: Epidemiology, treatment, complications, and rehabilitation. A review - Yana O. Gabueva; Yulia A. Kulakova; Natalya A. Buralkina; Anton A. Gorpenko; Vladimir D. Chuprynin; Dmitry L. Ovodenko (ZAO "Consilium Medicum", 2024)
Background. Cervical cancer (CC) is a malignant neoplasm of external localization, with incidence ranking 5th among genital tumors in Russia. A significant part of the cases involve women of working age. The management of cervical cancer depends on the stage of the disease, as well as the age and comorbidities. In most cases, radical surgery or chemoradiotherapy is performed alone or in various combinations. Surgery may include conization/amputation of the cervix, radical trachelectomy, or hysterectomy of various types, depending on the tumor stage. The interventions involve the resection of 2/3 of the vagina and the removal of parametrium at the level of the musculoskeletal walls of the pelvis minor. These types of interventions are traumatic and can lead to a deterioration in the quality of life of patients. Aim. To analyze available rehabilitation methods for patients undergoing radical treatment for cervical cancer. Materials and methods. The review presents data from Russian and foreign articles on this topic in the PubMed system. Results. There are various surgical and non-surgical methods for correcting a short vagina in congenital malformations. However, there is still no universal and comprehensive approach to solving this issue in women after surgery for cervical cancer. Conclusion. Cervical cancer remains one of the most serious medical and social problems of modern society. The very fact of diagnosis, which poses a threat of disability, social isolation, and death, as well as the antitumor treatment, negatively affects the physical and psycho-emotional state of women, significantly worsening their quality of life. Vaginal correction should be the next stage of postoperative treatment to restore sexual relations. However, the decision to use a particular method must be made in cooperation with the patient, considering all the risks and benefits for a particular case.